Proceedings of the 8th IEEE International Conference on Collaborative Computing: Networking, Applications and Worksharing 2012
DOI: 10.4108/icst.collaboratecom.2012.250499
|View full text |Cite
|
Sign up to set email alerts
|

Reputation Management in Crowdsourcing Systems

Abstract: Worker selection is a significant and challenging issue in crowdsourcing systems. Such selection is usually based on an assessment of the reputation of the individual workers participating in such systems. However, assessing the credibility and adequacy of such calculated reputation is a real challenge. In this paper, we propose a reputation management model which leverages the values of the tasks completed, the credibility of the evaluators of the results of the tasks and time of evaluation of the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…For social networks and crowdsourcing platforms it is already identified that trust is important in deciding with whom to establish connections and with whom to interact [8], [22], [2]. We stress that this importance is even higher in SCUs because they entail complex, structures and organized work.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For social networks and crowdsourcing platforms it is already identified that trust is important in deciding with whom to establish connections and with whom to interact [8], [22], [2]. We stress that this importance is even higher in SCUs because they entail complex, structures and organized work.…”
Section: Introductionmentioning
confidence: 89%
“…As far as we know, online social trust in the context of Human Computation [14] is only explicitly investigated in the context of social networks such as in [22] and [8], the Crowdsourcing context [2], as well as in human-enhanced service oriented environments on individual worker-basis [16]. However, there is no trust investigation based on metrics relevant for task-executing elastic collectives of human based services such as SCUs, although there is some work on trust in virtual teams (e.g., [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Quality in crowdsourcing is always under question. The reason is that workers in crowdsourcing systems have different levels of expertise and experiences; they contribute with different incentives and motivations; and even they might be included in collaborative unfair activities [33,42,43]. Several approaches are proposed to assess quality of workers' contributions such as expert review, input agreement, output agreement, majority consensus and ground truth [33].…”
Section: Dimensionsmentioning
confidence: 99%
“…The reputation score and expertise of workers are built based on the history of a participant, i.e., the quality of contributions of the participant in the previous tasks. Since the number of accomplished tasks for such a participant is small, the parameters and attributes that are computed based on such a short or sparse history should have a lower credibility [2]. Recall that is the engagement probability of a the participant .…”
Section: Recruitment Unitmentioning
confidence: 99%